Uterine Fibroid Patients Reveal Alterations in the Gut Microbiome - Mao, Xuetao; Peng, Xuan; Pan, Qiong; Zhao, Xingping; Yu, Zheng; Xu, Dabao (Frontiers in Cellular and Infection Microbiology, 2022)
The gut microbiota is associated with reproductive disorders in multiple ways. This research investigated possible differences in gut microbiome compositions between patients with uterine fibroids (UFs) and healthy control subjects in order to further provide new insight into its etiology. Stool samples were collected from 85 participants, including 42 UF patients (case group) and 43 control subjects (control group). The gut microbiota was examined with 16S rRNA quantitative arrays and bioinformatics analysis. The α-diversity in patients with UFs was significantly lower than that of healthy controls and negatively correlated with the number of tumorigeneses. The microbial composition of the UF patients deviated from the cluster of healthy controls. Stool samples from patients with UFs exhibited significant alterations in terms of multiple bacterial phyla, such as Firmicutes, Proteobacteria, Actinobacteria, and Verrucomicrobia. In differential abundance analysis, some bacteria species were shown to be downregulated (e.g., Bifidobacteria scardovii, Ligilactobacillus saerimneri, and Lactococcus raffinolactis) and upregulated (e.g., Pseudomonas stutzeri and Prevotella amnii). Furthermore, the microbial interactions and networks in UFs exhibited lower connectivity and complexity as well as higher clustering property compared to the controls. Taken together, it is possible that gut microbiota dysbiosis has the potential as a risk factor. This study found that UFs are associated with alterations of the gut microbiome diversity and community network connectivity. It provides a new direction to further explore the host–gut microbiota interplay and to develop management and prevention in UF pathogenesis.